Self-rotatory performance of conical cutter interacted with rock material. (October 2017) - Liu, Xiaohui; Tang, Ping; Li, Xuan; Tian, Mingrui
Abstract: Conical cutters work on high impact and stress condition, which easily results in failure. The percentage of failure due to wear is about 75%. More importantly, self-rotatory ability of conical cutters is the key factor on its wear. However, the mechanism of self-rotatory has not been further studied until now. Thus, firstly in this paper, three probable rotating states of cutter interacted with rock material were analyzed in theory, and the hypotheses about influence of rotary kinetic and resistance torque were proposed. Then, the influence of cutting types, working angle parameters and structural parameters on self-rotatory performance of cutter was studied using cutting test-bed for rock material. The experiment results indicate that, conical cutters really have self-rotatory ability when interacted with rock material, which owes to asymmetrical cutting load; the rotatory angle of cutter decreases gradually with cutting angle, and increases with incline angle; the change of rotatory angle caused by cutting angle is about 60°, while almost 360° for incline angle when the rotation angle of cutter is less than 360° in a certain cutting time; the rotatory angle almost shows a linear increasing trend with cutter-body length and the interval between cutter-handle and cutter-holder, decreases linearly with cutter-handle length, while increases at first and then decreases with cutter-handle diameter; among these four structural parameters, the influence of interval between cutter-handle and cutter-holder is greatest about 200°, followed by cutter-body length, and the last is cutter-handle length and cutter-handle diameter. At last, comparing the experiment results and hypotheses about influence of rotary resistance torque, it can be seen that, the dominant factor on self-rotatory ability of cutter is not friction resistance between cutter and cutter-holder but the duration that cutter with no rotary resistance torque. Graphical abstract: Highlights: Probable rotating states of cutter interacted with rock were analyzed in theory. The hypotheses about influence of rotary kinetic and resistance torque were proposed. Self-rotatory performance of cutter was studied using cutting test-bed for rock material.